2015
DOI: 10.1111/jvim.13608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Electrochemical Point‐of‐Care Meter for Measuring Glucose Concentration in Blood from Periparturient Dairy Cattle

Abstract: BackgroundThe Precision Xtra® meter is a promising low cost electrochemical point‐of‐care unit for measuring blood glucose concentration ([gluc]) in cattle blood. The meter uses an algorithm that assumes the intra‐erythrocyte [gluc] equals the plasma [gluc] on a molal basis, and that the hematocrit is similar in humans and cattle.ObjectivesThe primary objective was to determine the accuracy of the meter for measuring plasma [gluc] in dairy cattle. Secondary objectives were to characterize the influence of hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 45 publications
3
36
2
Order By: Relevance
“…The study reported here was part of a larger study investigating energy and potassium homeostasis in the periparturient period, and the prediction of parturition and dystocia in Holstein–Friesian cattle. These results have been published elsewhere …”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…The study reported here was part of a larger study investigating energy and potassium homeostasis in the periparturient period, and the prediction of parturition and dystocia in Holstein–Friesian cattle. These results have been published elsewhere …”
Section: Methodssupporting
confidence: 55%
“…Plasma [gluc] was measured using a Precision Xtra point‐of‐care meter. Plasma [gluc] was calculated from the Precision Xtra reading for plasma [gluc] in mg/dL ([gluc] p‐meter ) using the following equation developed by our laboratory: true[gluctrue] = 0.66×true[gluctrue]pmeter+ 15. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were obtained daily from the coccygeal vein or artery at approximately 09:00 am on days À4, À3, À2, À1, 0, 1, 2, 3, 7, 14, 21, and 28 relative to calving (day 0), as described elsewhere. 39 The study reported here was part of larger study investigating energy, calcium, and potassium homeostasis in the periparturient period, and the prediction of parturition and dystocia in Holstein-Friesian cattle. Further results have been published elsewhere.…”
Section: Measurement Of Blood B-hydroxybutyrate Concentrationmentioning
confidence: 99%
“…Further results have been published elsewhere. [39][40][41][42] Immediately after blood collection, BHB was measured in a drop of nonheparinized blood from the tip of the vacutainer needle using an electronic hand-held meter (Precision Xtra; Blood Glucose and Ketone Monitoring System; Abbott Diabetes Care Inc., Alameda, CA, USA). Both coded ketone test strips that included a calibrator strip with each new box of test strips, and noncoded ketone test strips were used.…”
Section: Measurement Of Blood B-hydroxybutyrate Concentrationmentioning
confidence: 99%